Prejudice and Inclusiveness in Adolescence: The Role of Social Dominance Orientation and Multiple Categorization. Issue 4 (31st July 2019) - Albarello, Flavia; Crocetti, Elisabetta; Rubini, Monica
Abstract : This study examined the relations of multiple categorization and social dominance orientation with adolescents' prejudice against migrants and identification with the human group over time. Participants were 304 Northern‐Italian late adolescents (61.84% female, M age  = 17.49) involved in a three‐wave longitudinal study (with 3 months interval between waves). Results showed that multiple categorization was negatively linked to prejudice at a later time, whereas social dominance orientation was positively associated with it; prejudice also negatively affected multiple categorization and positively affected social dominance orientation at a later time. Moreover, prejudice mediated the effects of multiple categorization and social dominance orientation on human identification. These findings have important implications suggesting the construens effect of multiple categorization for enhancing social inclusiveness.